Community species diversity mediates the trade‐off between aboveground and belowground biomass for grasses and forbs in degraded alpine meadow, Tibetan Plateau. Issue 19 (29th August 2021) - Zhou, Tiancai; Sun, Jian; Zong, Ning; Hou, Ge; Shi, Peili
Abstract: Although many empirical experiments have shown that increasing degradation results in lower aboveground biomass (AGB), our knowledge of the magnitude of belowground biomass (BGB) for individual plants is a prerequisite for accurately revealing the biomass trade‐off in degraded grasslands. Here, by linking the AGB and BGB of individual plants, species in the community, and soil properties, we explored the biomass partitioning patterns in different plant functional groups (grasses of Stipa capillacea and forbs of Anaphalis xylorhiza ). Our results indicated that 81% and 60% of the biomass trade‐off variations could be explained by environmental factors affecting grasses and forbs, respectively. The change in community species diversity dominated the biomass trade‐off via either direct or indirect effects on soil properties and biomass. However, the community species diversity imparted divergent effects on the biomass trade‐off for grasses (scored at −0.72) and forbs (scored at 0.59). Our findings suggest that plant communities have evolved two contrasting strategies of biomass allocation patterns in degraded grasslands. These are the "conservative" strategy in grasses, in which plants with larger BGB trade‐off depends on gigantic roots for soil resources, and the "opportunistic" strategy in forbs, in which plants can adapt to degraded lands using high variation and optimal biomass allocation. Abstract : Two contrasting strategies of biomass allocation patterns were detected in grasses and forbs. "Conservative" strategy in grasses, in which plants with belowground trade‐off depend on gigantic roots for soil resources. "Opportunistic" strategy in forbs, in which plants can adapt to degraded lands via high variation and optimal biomass allocation.